A promising catalyst for exclusive para hydroxylation of substituted aromatic hydrocarbons under UV light. Issue 18 (18th August 2017) - Das, Vijay Kumar; Gogoi, Satyabrat; Choudary, Boyapati Manoranjan; Karak, Niranjan
Abstract : Herein, we describe a waterborne polymer/carbon dot nanocomposite system as an efficient, resourceful and sustainable photocatalyst for para -selective hydroxylation of substituted aromatic compounds using H2 O2 under UV light. Abstract : Herein, we describe a waterborne polymer/carbon dot nanocomposite system as an efficient, resourceful and sustainable photocatalyst for para -selective hydroxylation of substituted aromatic compounds using H2 O2 under UV light. The polymer matrix and carbon dot generate a synergistic catalytic system. A unique structural attribute of the functionalities in this catalytic system attracts the aromatic substrates into close proximity and activates them. Additionally, the flexible molecular box-like structure of the hyperbranched polymer provides the ability for favorable three-point interaction with several substrates having various sizes by means of their multiple force networks and the increased accessibility of the active sites. The catalyst can be stored on the bench top for months and is reusable without considerable loss in its activity. The reaction was exclusively selective toward para hydroxylation irrespective of the nature of the substituents (electron donating or electron withdrawing) in the aromatic hydrocarbons. Hence, it is one of the most promising catalysts for selective hydroxylation of substituted aromatic hydrocarbons.